BASIC IMPERATIVES OF ELECTRICITY QUALITY MODELING - BERIDZE, TETIANA; SINCHUK, IGOR; FEDOTOV, VLADISLAV; KOTYAKOVA, MARINA; SHEPELEV, KOSTYANTYN (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The establishment of market relations in the electric power industry leads to the fact that electric energy is considered as a commodity that must meet a certain quality. The relevant legislative acts determine the responsibility of electric power sales organizations and electricity suppliers to consumers for the reliability and quality of their electric energy supply in accordance with technical regulations and other mandatory requirements. At mining enterprises, the issue of electric energy quality has become acute, since in modern conditions, the extraction of minerals is largely determined by significant electricity consumption. Scientific research in the direction of modeling electric energy quality is mostly aimed at determining the relevant technical characteristics. The proposed methodology for research and building a mathematical model is based on the assumption that the corresponding quality is inherent in the cost indicators of EE. At present, there is a need to take into account the interests of EE consumers regarding the cost of EE. Thus, a dual task is formed. From the point of view of ensuring the highest quality of consumed electric energy during the day, it is important that its consumption corresponds to the lowest cost according to the price schedule on the intraday market. This makes it possible to mathematically formulate the corresponding task. Knowing the grid of electricity tariffs during the day and the required volume of electricity consumption per day, it is possible to distribute the costs of this volume of electricity per day in such a way that the total amount of electricity consumption is minimal. This approach to the use of electricity makes it possible to save electricity, that is, to ensure its appropriate quality with rational use. The formed mathematical model opens the way to its widespread application in practice. The given example proved the feasibility and possibility of using the proposed methodology.